Biomechanical analysis of back-somersault kicks in taekwondo - Kim, Y. K.; Jung, J. Y.; Ju, J. Y.; Park, J. Y.; Kim, H. K.; Baek, C. E. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This study was purposed to investigate biomechanical differences between best and worst trials in performing back-somersault kicks in Taekwondo. Six elite members of college Taekwondo demonstration team participated in this study and executed each ten trials of single back-somersault kick and double back-somersault kick, respectively. High speed motion capturing system collected positions of 21 markers on major anatomical locations to obtain motion data of full body segments. After post-processing procedure, results showed that the best trial of back-somersault kicks indicated longer preparation time (countermovement), larger range of motions of hip joint, and higher peak angular velocities of knee and hip joints prior to take-off than those of the worst trial. We concluded that athletes should avoid a quick countermovement before take-off, which induces insufficient strain energy of lower extremities and ground reaction impulse. Therefore, a sufficient time for muscle contractions are required to develop high power.